Sosialisasi Pembayaran Pajak Bumi dan Bangunan pada Warga Desa Kedungpring - Rita Nataliawati; Mesra Berlyn Hakim; Afifah Nur Rosyidah (BADAN PENERBIT STIEPARI PRESS, 2021)
Taxes are levied based on legal norms to cover the costs of collective production of goods and services to achieve the general welfare and to enhance the development of a country. One source of tax funds comes from the Land and Building Tax. Refusal to pay, avoidance, or resistance to taxes is generally a violation of the law. Tax is a source of government funds for development, both central and local governments. If a person has fulfilled the subjective and objective requirements, then he is obliged to pay taxes. However, the problem that is often faced by the government is the lack of awareness of taxpayers regarding the obligation to pay taxes. In this community service, the Institut Teknologi dan Bisnis Ahmad Dahlan team carried out socialization activities regarding the payment of Land and Building Tax in Kedungpring Village as one of the steps to increase public awareness in Lamongan Regency.